Impact and effectiveness of transport policy measures for a renewable-based energy system. (October 2019) - Venturini, Giada; Karlsson, Kenneth; Münster, Marie
Abstract: The unsustainable growth in global transport activity is straining planet's resources and ecosystems. Hence, there is a need to promote technological developments, regulatory instruments and social changes to reduce the impact of mobility demand on energy use and environment. The current paper aims at assessing the impact and effectiveness of transport policy measures in reaching emission reduction targets for the case of the integrated energy and transport system of Denmark. Our analysis of policy scenarios is performed in collaboration with experts, stakeholders and citizens, and facilitated by a newly developed Scenario Interface tool linked to the energy system model TIMES-DK. Market signals, in the form of taxes on CO2 and fossil fuels, retain the highest impact in lowering the carbon emissions from the transport sector, while the promotion of Mobility-as-a-Service is the most cost-effective measure among those analysed. Finally, we discuss the implications of combining instruments into policy packages and emphasise the urgency of addressing technology and policy solutions for the maritime and aviation sectors. Highlights: Impact and effectiveness of transport and energy policies are investigated. Participatory scenario development facilitated by Scenario Interface tool. Analysis of policy interaction in the optimization model TIMES-DK.